Wind tunnel tests of aerodynamic interference effects on two iced vertical circular cylinders in a tandem arrangement. (6th December 2021) - Li, Shengli; Han, Ruiqing; Guo, Pan; Wang, Xidong; Chu, Yajie
Abstract: The aerodynamic characteristics of the two iced vertical circular cylinders in a tandem arrangement, due to the shape change by icing, are complex, and lack systematical investigation. Therefore, a set of wind tunnel tests were carried out to study the aerodynamic characteristics of the leeward vertical cylinder, with ice shape, icing thickness, cylinder spacing, and icing relative position of cylinders varied in the subcritical Reynolds number range in this study. Results show that the icing thicknesses had a greater impact on the lift coefficients of D-shaped ice leeward cylinder at the same angle of attack. The aerodynamic characteristics of the iced leeward cylinder were stable when the ratio ( L/D ) of cylinder spacing was within the range of 4.8–6.2. The change of flow field should be considered in the stability analysis of two circular vertical cylinders. The drag coefficients of the iced leeward cylinder varied significantly due to the shielding effects, especially within the range of 9° attack angle and L < 6.2 D . The results of this work can provide an experimental reference for future research on wind resistance of two circular cylindrical structures in engineering practice.